2019
DOI: 10.24853/elif.1.2.89-94
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Understanding on Simple Past Tense through VOA Learning English YouTube Channel

Abstract: The objective of the study is to find out the effect of VOA Learning English YouTube Channel on students’ simple past tense. This study was conducted at 8th grade students of SMP Pustek Serpong in academic year 2017/2018. The researcher used quantitative analysis with a quasi-experimental design. As the sample, the researcher uses one class with total number of 37 students. By using t-test, the finding showed that tcalculation (7.89) was higher than ttable (2.026) at a significant level of 5%. It indicates tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…A new finding was found, which is that it eases students to understand sentence function, helping them to write and speak English. Moreover, their assignments can be done well with the learning using YouTube videos compared to the study of Mahmudah & Izzah (2019) that focuses on the aspect of students' understanding of simple past tense only. This study is also able to solve the problem of non native students during ODL for English subject similar to what is in the study of Tolkach & Pratt (2021) but it focuses more on tourism and hospitality.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A new finding was found, which is that it eases students to understand sentence function, helping them to write and speak English. Moreover, their assignments can be done well with the learning using YouTube videos compared to the study of Mahmudah & Izzah (2019) that focuses on the aspect of students' understanding of simple past tense only. This study is also able to solve the problem of non native students during ODL for English subject similar to what is in the study of Tolkach & Pratt (2021) but it focuses more on tourism and hospitality.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…It means that there are significant differences in teaching English grammar with VOA YouTube English Channel. It can be concluded that the use of VOA YouTube English Channel improves students understanding in simple past tense (Mahmudah & Izzah, 2019). COVID-19 pandemic has had an immense impact on all spheres of life including education.…”
Section: Literature Review Youtube In English Learningmentioning
confidence: 99%
“…Studies in the past discovered that incorporating VOA Learning English in classrooms contributed to learners' improvements in various aspects of English language teaching. A study conducted by Mahmudah and Izzah (2019) explored that VOA Learning English YouTube channel significantly improved students' understanding of simple past tense. Researchers also found that the VOA Learning English website videos efficiently honed students' speaking skills (Nguyen, 2018;Sulastri & Arina, 2018), meaning that VOA Learning English could improve more than students' grammatical features.…”
Section: The Use Of Voa Learning Englishmentioning
confidence: 99%
“…Previous study reported that students were found to exhibit errors when it comes to writing recount text in which simple past tense is the core. Errors in writing simple past tense through various texts including narrative and recount text has been reported in high school and college settings (Burhan, 2019;Chan, 2016;Devie et al, (2019); Kristiani Br Ginting & Purwanto, 2019a;Mahmudah, (2017); Nurul Amla, (2022). ; Situmeang et al, 2021;Umar, 2015;Wahyuningtyas & Bram, 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the negative and interrogative sentences are constructed through the emergence of the "did" as auxiliary verbs. Whenever "did" appears in the sentence, the verbs will turn into the infinitive (see more in Mahmudah, 2017.). Apparently, all these formulas have put more challenges to students as to why many of them fail in writing the grammatically correct simple past tense sentence.…”
Section: Introductionmentioning
confidence: 99%